ECgo: All-optical induction of single endothelial cell injury and capillary occlusion in the brain - Jacqueline Condrau; Srinivasa R. Allu; Tatiana V. Esipova; Eva Erlebach; Matthias T. Wyss; Chaim Glück; Luca Ravotto; Thomas Troxler; Mikhail Drobizhev; Marco Villa; Paola Ceroni; Mohamad El Amki; et al. (Proceedings of the National Academy of Sciences, 2026)
The ability to induce endothelial cell (EC) damage in the mouse brain with high spatial precision is invaluable for mechanistic studies of brain capillary injury and repair. Here, we introduce an optical method, termed Endothelial Cell guided obliteration (ECgo), that utilizes a two-photon-excitable porphyrin-based photosensitizer ( Ps2P ) to selectively obliterate single ECs within the brain microvascular network. Using the developed approach, we were able to induce occlusions of single capillaries with high spatiotemporal control, while preserving the surrounding tissue. Combined with longitudinal two-photon imaging, ECgo enables studies of morphological and functional consequences of targeted single capillary EC injury in vivo under healthy and diseased conditions.